Merging Electronic Health Record Data and Genomics for Cardiovascular Research: A Science Advisory From the American Heart Association. (April 2016) - Hall, Jennifer L.; Ryan, John J.; Bray, Bruce E.; Brown, Candice; Lanfear, David; Newby, L. Kristin; Relling, Mary V.; Risch, Neil J.; Roden, Dan M.; Shaw, Stanley Y.; Tcheng, James E.; Tenenbaum, Jessica; et al.
Abstract : The process of scientific discovery is rapidly evolving. The funding climate has influenced a favorable shift in scientific discovery toward the use of existing resources such as the electronic health record. The electronic health record enables long-term outlooks on human health and disease, in conjunction with multidimensional phenotypes that include laboratory data, images, vital signs, and other clinical information. Initial work has confirmed the utility of the electronic health record for understanding mechanisms and patterns of variability in disease susceptibility, disease evolution, and drug responses. The addition of biobanks and genomic data to the information contained in the electronic health record has been demonstrated. The purpose of this statement is to discuss the current challenges in and the potential for merging electronic health record data and genomics for cardiovascular research.